2021
DOI: 10.3233/ch-211134
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound evaluation of a refractory ovarian endometrial cyst and ultrasound-guided aspiration sclerotherapy using urokinase and lauromacrogol

Abstract: Endometriosis is one of the most common diseases that happen in reproductive women. The main symptoms include ovarian endometrial cyst, pelvic pain, and so on. We report a case of a 23-year-old woman with a refractory long-course ovarian endometrial cyst (OEC). The patient was previously identified to have a hypoechoic mass sized 9.7 cm in diameter on ultrasound (US) in the right ovary and was tentatively diagnosed as OEC in another tertiary hospital, who was then subjected to US-guided cyst sclerotherapy whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A preliminary experimental study showed that lauromacrogol injection produced significant regression of endometrial foci ( 58 ). Ultrasound-guided aspiration sclerotherapy using lauromacrogol is a successful and effective treatment for refractory long-course ovarian endometrial cysts ( 59 ). In the present case, the functional endometrial tissue within the lesion was completely ablated by lauromacrogol, and the muscle layer surrounding the lesion was not damaged, retaining the integrity of the uterine wall.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary experimental study showed that lauromacrogol injection produced significant regression of endometrial foci ( 58 ). Ultrasound-guided aspiration sclerotherapy using lauromacrogol is a successful and effective treatment for refractory long-course ovarian endometrial cysts ( 59 ). In the present case, the functional endometrial tissue within the lesion was completely ablated by lauromacrogol, and the muscle layer surrounding the lesion was not damaged, retaining the integrity of the uterine wall.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ultrasound‐assisted thrombolysis (UAT) has emerged as a potential strategy to mitigate bleeding issues linked to conventional thrombolytic drugs while significantly enhancing therapeutic efficacy at lower doses 6 . The interplay between ultrasound (US) and UK has garnered significant attention in recent medical research, particularly in the context of thrombolysis and targeted drug delivery 7–10 . An ultrasound‐responsive nanoliposome capsule has been developed for the controlled release of UK, aimed at treating acute pulmonary embolism, that uses the ultrasonic cavitation effect and a sonosensitizer to generate singlet oxygen that breaks the bond in the liposome, thereby rapidly releasing UK 8 .…”
Section: Introductionmentioning
confidence: 99%
“…6 The interplay between ultrasound (US) and UK has garnered significant attention in recent medical research, particularly in the context of thrombolysis and targeted drug delivery. [7][8][9][10] An ultrasound-responsive nanoliposome capsule has been developed for the controlled release of UK, aimed at treating acute pulmonary embolism, that uses the ultrasonic cavitation effect and a sonosensitizer to generate singlet oxygen that breaks the bond in the liposome, thereby rapidly releasing UK. 8 US combined with UK and Arg-Gly-Asp sequence (RGDS)targeted microbubbles in a rabbit model showed that complete recanalization could be achieved, with histological observations confirming the effective dissolution of thrombi.…”
mentioning
confidence: 99%
“…Lauromacrogol is a novel agent for blood vessel hardening that is widely applied in the sclerotherapy of multiple diseases, including hemangioma, venous malformations, ovarian cysts, uterine fibroids, and varicosity (11)(12)(13)(14). It can provoke endothelial maceration and destroy the cellular elements by acting as a detergent on the phospholipid layer of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…It can provoke endothelial maceration and destroy the cellular elements by acting as a detergent on the phospholipid layer of the cell membrane. This medicine has no mutagenic, carcinogenic, or embryotoxic effect and will not produce pain or extravasation necrosis (11)(12)(13)(14). Currently, there are only two reports of the use of lauromacrogol in managing CSP as a safe, novel therapeutic approach for CSP (2,14).…”
Section: Introductionmentioning
confidence: 99%